2016
DOI: 10.1039/c6cp05135a
|View full text |Cite
|
Sign up to set email alerts
|

Fe–Si networks in Na2FeSiO4 cathode materials

Abstract: Using a combination of adaptive genetic algorithm search, motif-network search scheme and first-principles calculations, we have systematically studied the low-energy crystal structures of Na2FeSiO4. We show that the low-energy crystal structures with different space group symmetries can be classified into several families based on the topologies of their Fe-Si networks. In addition to the diamond-like network which is shared by most of the low-energy structures, another three robust Fe-Si networks are also fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…16 Na-based orthosilicates are also known to exhibit a greater structural stability upon cycling with respect to their lithium counterparts, 15,18 due to the high Na/Fe exchange barriers observed for equilibrium structures exhibiting a diamond-like arrangement of AO 4 (A = Fe, Si) tetrahedral blocks. 12 DFT studies of these structures report also a very small volume change (below 3%) upon complete desodiation. 12 Experimental studies are overall in agreement with the predicted structural stability, 15,18,19 observed only when control over impurities is achieved 14 .…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…16 Na-based orthosilicates are also known to exhibit a greater structural stability upon cycling with respect to their lithium counterparts, 15,18 due to the high Na/Fe exchange barriers observed for equilibrium structures exhibiting a diamond-like arrangement of AO 4 (A = Fe, Si) tetrahedral blocks. 12 DFT studies of these structures report also a very small volume change (below 3%) upon complete desodiation. 12 Experimental studies are overall in agreement with the predicted structural stability, 15,18,19 observed only when control over impurities is achieved 14 .…”
mentioning
confidence: 91%
“…12 DFT studies of these structures report also a very small volume change (below 3%) upon complete desodiation. 12 Experimental studies are overall in agreement with the predicted structural stability, 15,18,19 observed only when control over impurities is achieved 14 . In 2011, Duncan and coworkers first successfully synthesised Na 2 MnSiO 4 (space group Pc) using a sol-gel method.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The concept has been generalized to LiFePO4 systems by Lv et al where Fe-P networks are used to predict new low-energy structures with remarkable success 19 . Following previous work 21 , the Fe-Si networks in low-energy LiFeSiO4 structures are classified into 2D-ladder-like, 3D-diamond-like and 3D*-4-8-membered-rings types (For simplicity, we use name "2D", "3D" and "3D*" in the following discussion) according to the FeSi4 and SiFe4 polyhedra which are considered as building blocks of the Fe-Si networks ( fig.1).…”
Section: Introductionmentioning
confidence: 94%
“…A common diamond-like Fe-Si network was found for most of the lowenergy structures of Na2FeSiO4. The electrochemical properties are also related to the type of Fe-Si networks: crystal structures with common Fe-Si networks have similar electrochemical behaviour from first principles calculations 21 . The concept has been generalized to LiFePO4 systems by Lv et al where Fe-P networks are used to predict new low-energy structures with remarkable success 19 .…”
Section: Introductionmentioning
confidence: 99%